Influence Quantity Earthworm (Lumbricus Sp.) on Various Changes Basic Soil Quality Physical Parameters in Peat Pool - Asto Saputro; Syafriadiman '; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in December 2015 to January 2016. The aim of this study was to determine the influence of the quantity of worms (tail/m2) to change some basic physical parameters of soil quality peat pond was. The method used in this study is an experimental method by using a completely randomized design (CRD) that is using one factor, the level 5 treatments and 3 replications. The treatmen such as; P0: without earthworms, P1: 200 earthworms / m2 extensive media maintenance, P2: 400 earthworms / m2 extensive media maintenance, P3: 600 tail earthworms / m2 extensive media maintenance, P4: 800 animals earthworms / m2 extensive media maintenance, P5: 1000 tail earthworms / m2 extensive maintenance media. The production of vermicompost highest average is in P5 at 216, 43 g.Keyword: Earthworm, Physical Parametres, Earth Quality, Peat Pool